Training Technologies as a Means of Forming Sustainable Development Competencies in Future Primary School Teachers - Chaikovska, Hanna (Educological discourse, 2023)
The article deals with the role of training technologies in teaching higher education students of the educational and professional program "Primary Education" for sustainable development. The research is dedicated to the meaning of the term "training technologies", analyses approaches to the definition of the studied concept. In accordance with the content of the sustainable development concept, it were identified trainings in environmental, economic and social areas and it was developed the training programme called "Challenges of Sustainable Development: Learning Sustainability". The main goal of the proposed trainings is to form in future primary school teachers’ knowledge, practical skills and abilities of sustainable development, to develop their ability to make decisions in the interests of sustainable development and to be aware of their own responsibility for its achievement, to increase positive attitude to the role of teachers in achieving sustainable development of society, etc. The focus is made on the methods that are directly related to the formation of sustainable development competences of applicants for higher education. The focus is made on the methods that are directly related to the formation of sustainable development competences in applicants for higher education. It is proposed exercises and tasks for the future primary school teachers’ development systemic and critical thinking skills, self-reliance, collective interaction, professional skills, etc. The author’s training programme was tested during the study of the elective course "Education for Sustainable Development in Primary School". An experimental study was conducted with applicants for higher pedagogical education (students of Ternopil Volodymyr Hnatiuk National Pedagogical University) with the aim to study its impact on the improvement of sustainable development competences of future primary school teachers. Using the author’s methodology, the levels of key competences of sustainable development (systemic and prognostic thinking, cooperation, critical thinking, modelling sustainable behaviour) are determined before and after the experiment. After implementation the training programme, an increase in future teachers’ the level of development of the studied qualities was revealed. It is proved the positive impact of training technologies on the respondents’ development of sustainable development competencies.